2013 9th Asian Control Conference (ASCC) 2013
DOI: 10.1109/ascc.2013.6606039
|View full text |Cite
|
Sign up to set email alerts
|

Automotive longitudinal speed pattern generation with acceleration constraints aiming at mild merging using model predictive control method

Abstract: To ensure safety and simplicity in merging path generation for a realistic reliable and mild merging, this paper proposes a merging path generation method. In the proposed method, the merging problem is considered in two-dimensional space and formulated into a one-dimensional space optimization problem by relating the longitudinal motion of the merging vehicle to the lateral motion of it. In this way the optimization problem would be much simpler and therefore the computational time could be shorter than formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The other major category of strategies applies optimization. In a series of studies, [14,[22][23][24] formulated an optimal control problem governing cooperative driving of all mainline vehicles and on-ramp merging vehicles in a merge section. Although the authors used model predictive control (MPC), they did not really take the advantage of MPC's "closing-the-loop" feature, because all the vehicles are controlled by a centralized controller and thus no vehicle is an external disturbance and no prediction is really needed.…”
Section: A a Summary Of Existing Studiesmentioning
confidence: 99%
“…The other major category of strategies applies optimization. In a series of studies, [14,[22][23][24] formulated an optimal control problem governing cooperative driving of all mainline vehicles and on-ramp merging vehicles in a merge section. Although the authors used model predictive control (MPC), they did not really take the advantage of MPC's "closing-the-loop" feature, because all the vehicles are controlled by a centralized controller and thus no vehicle is an external disturbance and no prediction is really needed.…”
Section: A a Summary Of Existing Studiesmentioning
confidence: 99%
“…As a comparison, the simulation of this case is also conducted with the method proposed in Cao, Mukai, Kawabe, Nishira, and Fujiki (2013b), in which b was fixed at 0. The time histories of the variables are shown in Fig.…”
Section: Case 1: the Cooperative Merging Cao Et Al (2013a)mentioning
confidence: 99%
“…Goli and Eskandarian (2014) proposed an algorithm consisting of proportional-derivative and sliding mode controllers for merging operation in a platoon. The second group considered the merging control on a ramp (Cao et al 2013;Rai et al 2015;Sakaguchi et al 1997). Sakaguchi et al (1997) introduced a merging algorithm on a ramp based on the pole assignment technology and virtual vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Sakaguchi et al (1997) introduced a merging algorithm on a ramp based on the pole assignment technology and virtual vehicles. Cao et al (2013) suggested a scheme of merging control on a ramp based the model predictive control algorithm. Rai et al (2015) considered the artificial potential field for the design of the controller of merging operation.…”
Section: Introductionmentioning
confidence: 99%